PEMANFAATAN WORDWALL SEBAGAI MEDIA INTERAKTIF TERHADAP MINAT BELAJAR SISWA PADA PELAJARAN MATEMATIKA - Tia Suharto; Firdaus Ainul Yakin; Farich Purwantoro (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2025)
Interest in studying mathematics is one of the important things in improving student achievement, but in reality most students complain that they don't like mathematics lessons because they are considered difficult, scary and boring, so this requires innovation in teaching and learning activities, namely by using interactive wordwall media. The purpose of this research is to find out how the use of wordwall learning media for class II in mathematics subjects, multiplication material and to find out whether the use of wordwall media has an effect on students' interest in learning. The method applied in this research is a quantitative approach with descriptive research type and the assure development model. The results of the research show that the wordwall learning media shows that the wordwall learning media provides benefits in learning class II mathematics subjects in multiplication material, with an average score of 3.37 on the media use questionnaire, while the Pearson correlation analysis shows an r value of 0.65, which indicates a strong influence between the use of wordwall media on students' interest in learning, thus it can be concluded that wordwall is an effective media in increasing students' interest and understanding in mathematics learning multiplication material